The price level, relative prices, and economic stability: Aspects of the inter-war debate - David Laidler (The University of Western Ontario, Department of Economics, 2003)
Recent financial instability has called into question the sufficiency of low inflation as a goal for monetary policy. This paper discusses interwar literature bearing on this question. It begins with theories of the cycle based on the quantity theory, and their policy prescription of price stability supported by lender of last resort activities in the event of crises, arguing that their neglect of fluctuations in investment was a weakness. Other approaches are then taken up, particularly Austrian theory, which stressed the banking system's capacity to generate relative price distortions and forced saving. This theory was discredited by its association with nihilistic policy prescriptions during the Great Depression. Nevertheless, its core insights were worthwhile, and also played an important part in Robertson's more eclectic account of the cycle. The latter, however, yielded activist policy prescriptions of a sort that were discredited in the postwar period. Whether these now need re-examination, or whether a low-inflation regime, in which the authorities stand ready to resort to vigorous monetary expansion in the aftermath of asset market problems, is adequate to maintain economic stability is still an open question.
Keywords: 330